Risk management in large-scale information system projects - Castillo-Ñopo, Diego Armando; Loyola-Blanco, Khateryn Fiorela; Castro-Marca, Raul; Rosa-Gavino, Gian Davor La; Aragón-Retuerto, Jherson Giovanny; Rafael-Sifuentes, Hegel Alvaro; Marín Rodriguez, William Joel (EAI Endorsed Transactions on Scalable Information Systems, 2024)
This article deals with project management in information systems, whose relevance lies in the vital importance of these systems in modern companies. Information systems are essential for decision making and data management in today’s interconnected world. Project management, on the other hand, coordinates elements such as scope, resources, costs, schedules and risks to achieve defined objectives. The systems development life cycle (SDLC) structures the process, encompassing phases such as scope definition, planning, execution, monitoring and closure. These phases are integrated with risk management, which identifies, evaluates and mitigates threats and opportunities. Mitigation strategies act before adversity, while contingency planning prepares for the unforeseen. That is why risk management is integrated throughout the project life cycle to anticipate and address challenges. The combination of both aspects is critical in a constantly evolving technology environment. In addition, organizational culture and communication play a critical role. A culture of awareness and accountability, transparency in communication and active stakeholder participation are essential. Training and continuous adaptation allow learning from past experiences and improving practices.